How Should Consumption Be Taxed? - Spencer Bastani; Sebastian Koehne (Center for Economic Studies and ifo Institute (CESifo), 2022)
We review the theoretical justification of consumption taxes in advanced economies, providing a systematic overview of the vast public finance literature exploring how goods and services should be taxed. Our discussion focuses on both the determinants of the optimal level of consumption taxation in relation to other taxes, as well as the optimal differentiation of taxes across goods and services. We blend classical public finance results, recent developments in the optimal tax literature, as well as practical considerations. The purpose is to provide guidance to academics and policymakers about the key trade-offs in consumption taxation as well as point out important areas where more research is needed.
Keywords: H21; H24; 330; taxation; consumption; commodity; labor; capital; wealth